2016
DOI: 10.1161/jaha.116.003695
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Closure Under Intracardiac Echocardiographic Guidance: Feasibility and Comparison With Transesophageal Echocardiography

Abstract: BackgroundTranscatheter left atrial appendage closure is an alternative therapy for stroke prevention in atrial fibrillation patients. These procedures are currently guided with transesophageal echocardiography and fluoroscopy in most centers. As intracardiac echocardiography (ICE) is commonly used in other catheter‐based procedures, we sought to determine the safety and effectiveness of intracardiac echocardiography–guided left atrial appendage closure with the Watchman device.Methods and ResultsA total of 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 13 publications
4
48
0
Order By: Relevance
“…Of this series, 117 underwent successful LAA occlusion device implantation (96.7%), with a high correlation agreement of LAA dimensions assessed by angiography and ICE ( r = 0.94). More recently, Matsuo Y. et al reported a 100% success rate of LAA closure using the Watchman device with ICE guidance from the right atrium in 27 patients . Although the authors claimed that satisfactory images can be obtained from the right atrium, it is our experience that these ICE images are typically inferior in terms of quality than those acquired with the ICE probe positioned in the LA, which may lead to misleading information critical for appropriate device sizing and implantation.…”
Section: Discussionmentioning
confidence: 95%
“…Of this series, 117 underwent successful LAA occlusion device implantation (96.7%), with a high correlation agreement of LAA dimensions assessed by angiography and ICE ( r = 0.94). More recently, Matsuo Y. et al reported a 100% success rate of LAA closure using the Watchman device with ICE guidance from the right atrium in 27 patients . Although the authors claimed that satisfactory images can be obtained from the right atrium, it is our experience that these ICE images are typically inferior in terms of quality than those acquired with the ICE probe positioned in the LA, which may lead to misleading information critical for appropriate device sizing and implantation.…”
Section: Discussionmentioning
confidence: 95%
“…Transoesophageal echocardiography (TOE) is currently the gold standard imaging modality for the guidance of LAAO . However, intracardiac echocardiography (ICE) is now being used to guide a multitude of percutaneous interventions for structural heart disease and its utility in guiding percutaneous LAAO has been suggested by several studies …”
Section: Introductionmentioning
confidence: 99%
“…Although, ICE in the left atrium allows a good evaluation of Amulet or Watchman criteria for proper device deployment, the inability of ICE to systematically obtain a proper TEE 110‐135° plane is a significant limitation, since peridevice leaks are frequently best assessed in that view . Nonetheless, the safety results and outcomes of this transseptal ICE approach for LAA closure have been recently published and showed that ICE in the left atrium was noninferior to TEE regarding procedural success, major periprocedural complications or rate and degree of peridevice leaks. Also, the residual atrial septal defects at follow‐up were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%